Estimativa dos parâmetros hidrodinâmicos do sistema aquífero da região do Carste de Lagoa Santa por métodos diretos e indiretos - Matheus Alonso Castelo Pena (2023)
The aquifer system of the Lagoa Santa Karst Environmental Protection Area (APA), in Minas Gerais, Brazil, exhibits typical characteristics of an evolved karst environment, including extensive caves, sinkholes and voluminous springs, overlaying the crystalline basement. Understanding hydrogeological characteristics is crucial for the efficient management of water resources and the prevention of contamination, given the high vulnerability of this area. In this context, the evaluation of hydrodynamic parameters that influence subsurface flow becomes fundamental, especially considering the economic and population development of the region. This study uses direct (pumping test analysis) and indirect methods (capture zones and hydrograph analysis) to estimate hydrodynamic parameters, focusing on the transmissivity and storativity of the aquifer in the APA region and surroundings. The Agarwal Recovery method stands out among the direct methods due to its independence in relation to pumping time, minimizing errors related to flow variation. The Theis and Moench Double-Porosity methods also show satisfactory results, while the Neuman method proves to be inadequate for characterizing the region's karst aquifer. Furthermore, indirect methods demonstrate viability, however recommendations for their use are proposed. An equation is derived that relates transmissivity to the specific capacity of the well, which allows this parameter to be accessed more efficiently. Through this relationship, an interpolated surface of transmissivity and another of porosity are generated, allowing the identification of more karstified areas. Four zones of greater karstification are delimited, whose hydrodynamic parameters are defined, presenting considerable productivity and a concentration of important springs. Additionally, the transmissivity and storativity values for the alluvial and fissure aquifer are determined based on pumping tests, highlighting the importance of the alluvial aquifer in terms of productivity. The fissure aquifer is subdivided into a shallow portion with significantly higher productivity than the base portion. These conclusions have important implications for the sustainable management of groundwater resources in a complex karst environment, contributing to the understanding of hydrogeological behavior in the region.